Job satisfaction among the staffs of Tenaga Nasional Berhad (TNB) in Investment Management Division / Noorazlinda Mustapa - Mustapa, Noorazlinda (Faculty of Business and Management, 2006)
Job satisfaction is one of the evaluation aspects in work behavior, which has been emphasized by all of the organizations to ensure the successful of organization's goal. This research is focus on the job satisfaction among Investment Management Division staffs at Tenaga Nasional Berhad. Moreover, this study will examine and measure level of satisfaction among Investment Management Division staffs in the existing services, facilities that provide to them and help the management to identify the factors that influence job satisfaction among staffs. The findings showed that most of the staffs have moderate level of satisfaction with the work itself, supervision, co-worker and working condition. The researcher is also able to give some recommendations and suggestion on how to improve and increase job satisfaction of the staffs after the analysis, findings and interpretation. In this study, we used interviews and questionnaire techniques and others secondary data such as reports, database, and so on for data collection. Based on frequency, cross tabulation and Chi-Squared test, a clear findings and result is observed.